A 76-year-old male with abdominal cutaneous nerve entrapment syndrome: a case report - Kalanj, Karolina; Herceg, Matija; Ivanac, Antonio; Kalanj, Sara; Peček, Mirta; Brundula, Ana (Frontiers in Pain Research, 2025)
Abdominal pain represents a frequent presenting symptom in emergency departments, with up to 20% of patient visits involving abdominal and/or flank pain. Recently published studies indicate that anterior cutaneous nerve entrapment syndrome (ACNES) is a more common cause of these symptoms than previously believed, with up to 2% of patients presenting to the emergency department at teaching hospitals being ultimately diagnosed with the condition. Importantly, ACNES is often misdiagnosed as another cause of abdominal pain. We present a 76-year-old patient whose a chief complaint was persistent abdominal pain localized to the right side of the umbilicus over a 6-week period, associated with a burning sensation of the skin. Following unremarkable laboratory, imaging, and endoscopy findings, the diagnosis of ACNES was confirmed with simple Carnett's sign. This is the first documented report to highlight that interventional treatment when combined with exogenous factors can contribute to the repair of nerve damage.